MUNASABAH AYAT DALAM SURAH AL-QALAM PERSPEKTIF SEMITIC RHETORICAL ANALYSIS (SRA) - Sujiat Zubaidi; Dini Amalia Fattah; Aqdi Rofiq Asnawi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
Criticism of the Quran has been a part of Quranic studies for some time. One of the figures who criticized the Quran is Richard Bell, an orientalist, who, in his book titled "The Quran Translated, with a critical re-arrangement of the Surah," cast doubts on the authenticity of the Quran. Bell mentions the presence of added verses that are considered not in line with the original text, including in Surah al-Qalam, specifically in verses 10-16. Additionally, he also notes that verses 51-52 appear to lack relevance to the verses before or after them. The purpose of this research is to examine whether the structure of Surah al-Qalam exhibits symmetry in accordance with patterns of parallel, concentric, or mirror-symmetrical arrangements at various levels of the text. The research methodology employs analysis, which is used to process data and address the research questions. This research approach adopts the concept of "Coherence" to find coherence in the structure of surah al-Qalam using the Semitic Rhetorical Analysis methodology. This research is a type of library research, which involves collecting data from various sources such as books, scientific documents, journals, etc. The results of this research show that the application of Semitic Rhetorical Analysis in Surah al-Qalam produces a series consisting of 3 parts and 8 sections of text structure, which form a mirror concentric construction (AB/x/B’A’). The results of the analysis also show that there is a connection between parts, which shows good coherence and verse structure. This finding refutes Richard Bell's view because each verse in Surah al-Qalam is able to be symmetrical with other verses from the lowest to the highest text level